Green Leadership in The Spotlight: A Bibliometric Analysis of Research Developments - Murdiono, Jatmiko; Hamidah, Hamidah; Sariwulan, Tuty (IJHCM (International Journal of Human Capital Management), 2024)
Global sustainability issues require organizations to carry out strategic transformation by balancing profit, people, and planet aspects. In this context, green leadership is present as a leadership style that combines environmental orientation with management practices to support green innovation, sustainable performance, and environmentally oriented human resource management. This research aimed to provide a comprehensive overview of the development of green leadership research, identify trends, research gaps, and the direction of future academic collaboration. The research method uses a quantitative approach through bibliometric analysis with secondary data from the Scopus database using the keyword "green leadership". After the selection process based on the PRISMA framework, a total of 85 articles for the period 1993–2024 were analyzed using the VOSviewer software to map publication trends, affiliations, countries of origin of publications, scientific fields, and keyword relatedness. The results show that publications on green leadership have increased significantly, especially in the 2023–2024 period, with the dominance of the fields of management, social sciences, and environmental sciences. The keywords that are most often associated are sustainability, green innovation, corporate social responsibility, and green human resource management. This research shows that green leadership is increasingly relevant to answer global sustainability challenges. In the future, these findings can encourage the integration of green leadership in organizational policies, strengthen green HRM practices, and implement sustainable innovation in various industry sectors.